The Effect of Youtube Video on Students’ Vocabulary Mastery for Eighth Grade Students at SMP Negeri 1 Bangli - I Gede Bayu Upadana Anantawijaya; Ni Putu Ratni; I Putu Andre Suhardiana (Educational Journal, 2026)
This research was conducted to investigate the significant effect of YouTube videos on students’ vocabulary mastery for the eighth grade students at SMP Negeri 1 Bangli. This research was conducted with the quasi experimental design containing two group as experimental and control groups. The eighth grade students from SMP Negeri 1 Bangli were involved as the research population. The cluster random sampling technique was applied, that made class 8E and 8F became the selected sample. Participant of this research were split into 35 students in group experimental and for other 35 students in group control, numbering total  of 70 participant. Vocabulary test was used as the instrument delivered into pre-test and post-test. The form of the vocabulary test was a multiple choice questions, applied also to pre-test and post-test. The collected data from the research participant was analysed using independent sample t-test to determine the significancy of the data. From the independent sample result showed that, the students’ vocabulary mastery was showing significant effect after given the post test. As shown by the value of t (68) = 3.044, with p value = 0.003, which the p value was lower than 0.050 (0.000>0.050). Also proved by the post-test mean score from experimental group of 82,56 was greater than control group of 76.23. According to these finding, can be concluded that the vocabulary mastery of the students was effected significantly by YouTube videos for the eighth grade students at SMP Negeri 1 Bangli.